Peningkatan Loyalitas Pelanggan Melalui Strategi Digital Marketing Pada Wedding Flowsproject Decoration - Widhi Bayu Pribadi; Deny Yudiantoro (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the implementation and impact of digital marketing in strengthening customer loyalty through the AIDA concept (Attention, Interest, Desire, Action) in the wedding decoration services of Flowsproject Decoration. The research employs a descriptive qualitative method, with data collected through in-depth interviews with the business owner, direct observation of social media content on Instagram and TikTok (@flowsproject.decoration), and a comprehensive literature review. The findings reveal that AIDA-based digital marketing strategies are implemented effectively and consistently at every stage of the customer journey. Attention is captured through aesthetically curated and visually engaging content, while interest is developed through the display of diverse thematic portfolios and detailed project documentation. Desire is reinforced by offering integrated bundling packages and realistic 3D design visualizations tailored to client preferences. Finally, action is encouraged through a responsive communication system and persuasive call-to-action features. Overall, these strategies foster customer satisfaction, emotional connection, brand trust, service convenience, and long-term loyalty expressed through repeat orders and sustained word-of-mouth recommendations.